Efektivitas Perbedaan Komposisi Media Tanam dan Ukuran Belahan Bonggol pada Perbanyakan Pisang Susu (Musa paradisiaca var. Susu) Lokal Bali - SITI SHOFIAH; I NYOMAN RAI; NI NYOMAN ARI MAYADEWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Effectiveness of Differences in the Planting Media Composition and Corm Size in Bali Local Banana (Musa paradisiaca var. Milk) Propagation Banana (Musa paradisiaca) is one of the important commodities in Indonesia. Based on BPS Prov data. Bali (2017), the number of productive banana plants in Bali has decreased enormously, from 13,140,965 clumps in 2016 to only 4,681,879 clumps alone in 2017. The need for banana supply is so high when balinese people celebrate Galungan and Kuningan Ceremony. Banana needs that occur cannot be met because the production in Bali is low, not filled with production because of difficulty in obtaining seedlings, for that it is necessary to do research on the composition of planting media and the right size of banana chopped corm to provide good banana seeds. The growth and development of good banana plant seeds cannot be separated from the use of good planting media and the use of quality seeds. This study aimed to find out the interaction of planting media composition and the size of chopped corm in local Balinese susu bananas. This research was conducted at the experimental garden paranet house of the Faculty of Agriculture, Udayana University, Jl. Pulau Moyo No. 15 X, Pedungan, South Denpasar, Denpasar City, Bali from April to July 2020. The design used in this study is RandomIzed Block Design (RBD) Factorial pattern with 2 treatment factors, the first factor was the composition of planting media consists of 4 levels of treatment namely M1 (mixed media of soil and compost (1:1/V:V) 100% + burn husk 0%), M2 (mixed media of soil and compost (1:1/V:V) 75% + burn husk 25 %), M3 (mixed soil and compost media (1:1/V:V) 50% + 50% burn husks), M4 (mixed soil and compost media (1:1/V:V) 25% + burn husks 75%), M5 (mixed soil and compost media (1:1/V:V) 0% + 100% burn husks). The second factor was the size of the weevil hemisphere, consisting of 3 levels of treatment, namely B1 (size of corm hemisphere 4 x 4 x 4 cm), B2 (6 x 6 x 6 cm) and B3 (8 x 8 x 8 cm). The results showed that M3 media (mixed soil and compost media (1:1/V:V) 50% + 50% burn husks) was the composition of the planting media was best, the M3 treatment produces leaf chlorophyll, plant height, number of leaves, diameter of stems, time of root appear and the time the bud appears. B3 (8 x 8 x 8 cm) was the best size of banana weevil, B3 treatment produces leaf chlorine, plant height, number of leaves, stem diameter, root time and the best leaf appear time. There was an interaction between the combination of planting media (M) and the size factor of weevil (B) to the growth of susu banana seedlings, which is indicated by the time the bud appears, the time the root appears, the diameter of the stem, the height of the plant and the number of leaves. The best value was obtained on the M3B3 combination.